Evaluation the Effect of Fiber Reinforcement Materials on Flexural Strength of Heat Cured Denture Based Resin Materials - Reem M. Arif; Nagham H. Kassab; Ragheed kassab (University of Mosul, College of Dentistry, 2024)
Aims: To assess the effect of fiber reinforcement materials on the flexural strength of heat-cured denture-based resin. Materials and Methods: A sample of heat-cured acrylic resin was created and divided into a control group (heat-cured with no fiber addition) and two experimental groups (with fiber additive). The flexural strength was evaluated, and calculated. The information was statistically analyzed using descriptive statistics, an analysis of variance (ANOVA), and Duncan multiple range tests with p ≤ 0.01 in SPSS Version 19. Results: The result showed a significant increase in flexural strength, untreated polypropylene fibers showed the highest flexural strength followed by untreated glass fibers. Conclusion: Reinforcement with fibers was an efficient approach for the improvement of flexural strength of heat-cured PMMA denture base resin.